DIN NOU DESPRE PUBLICISTICĂ SAU DOUĂ ÎNTR-O BARCĂ: „PÂNĂ LA...” ŞI „DUPĂ...” - Guzun, Mihail (CEP USM, 2020)
Journalism and literature represent two types of creative interaction which cannot be questioned, even though different views have been exposed on this issue. The author says that in order to identify the mechanisms of interaction between journalism and literature, it is necessary to examine the place and role of a third component – journalism, the area that "meets both sides". The author uses also in the article examples of well-known writers’ creations from the local and international literature and for many of them journalism was the shortest way to literature. It is promoted the idea that in both journalism and literature the word is the working instrument, and the text’s writing is the ultimate purpose. This way, journalism should be considered as a genre of creative activity, as well as a form of literary work.
Keywords: literature; journalism; publishing; philology; word; journalistic education; literary skills